Effectiveness of Psychosocial Supportive Care Trial on Quality of Life among Breast Cancer Patients: An Interventional Study at the National Cancer Institute, Egypt - Ellawindi, Mona Ibrahim; Shoman, Tarek Hamed; Taher, Eman; Gohar, Sherif; Shehata, Samah (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Breast cancer (BC) patients suffer from many psychosocial problems due to their health condition and treatment side effects so they are in great need for psychosocial supportive care. AIM: The aim of the study was to provide a comprehensive psych-social supportive health-care model for BC patients a step toward improving their quality of life (QOL). PATIENTS AND METHODS: Random assignment was done for 185 patients with primary operated BC to a control or an intervention group. The researcher offered five daily successive psychosocial supportive care sessions for the patients in the intervention group. All patients were followed up for coping ability, mood and QOL 8 weeks after the intervention. RESULTS: The intervention had statistically significant effects on psychological distress, depression, problem focused, and active emotional coping domain, while had not any statistically significant effects on avoidant emotional coping domain. CONCLUSION: Psychosocial supportive developed health-care model decreased psychological distress, depression, and improved QOL among patients with primary BC.